PENDUGAAN PARAMETER DEMOGRAFI DAN PREFERENSI HABITAT TANGKASI (Tarsius lariang) DI KAWASAN TAMAN NASIONAL LORE LINDU - Abdul Rosyid (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Tarsius lariang, also called tangkasi is one of the endemic animals which is found in Lore Lindu National Park (LLNP). The threat to the tarsius population are the limitation of the distribution area, the escalation of forests exploitation, and hunting. People around the forest tend to think the tangkasi as a pest which eats cultivated plants. Therefore, population and habitat research is important. The purpose of this study is to estimate the demographic parameters and identify the characteristics of the habitat of the tangkasi, so that it can be known that the habitat component is important for the existence of the tangkasi in LLNP. The results of this study indicate the density of individual tangkasi across the LLNP region is 95.55 individuals per km². Individual density on Primary Dryland Forest Cover (PDFC) was 80.21 individuals per km² and in Dryland Secondary Forest (DSF) cover was 218.29 individuals per km², which still in normal level. The population density of tangkasi groups in the LLNP area is 35 groups per km², for the PDFC 32 and for the DSF of 54 groups per km². The total population of tangkasi based on age structure located in the research area of LLNP, PDFC, and DSF shows that the age of the juvenile is very low compared to the sub-adult age classes. It shows that tangkasi population is decreasing (regressive population). The preferred habitat of the tangkasi is the type of Dryland Secondary Forest (SDF) with a very steep slope of < 45% and altitude between 1301 and 1800 m asl.